Water relations of woody perennial plant species - Kenneth A. Shackel (OENO One, 2007)
Aims: To describe the relation of various water status measures of woody perennial plants (predawn and midday stem and leaf water potential), to indices of physiological activity such as leaf conductance, vegetative growth and fruit growth and composition. Methods and results: Almonds were exposed to three levels of irrigation over three years, and midday stem water potential (SWP) and leaf conductance, collected at approximately weekly intervals, is reported for the third year of the study. A strong linear increase in both leaf conductance and trunk growth occurred with increasing SWP, and this relation was consistent both within and between treatments. A similarly positive linear relation was found between SWP and fruit size in pear, with a negative relation between SWP and fruit soluble solids and fruit color. In grapevine, SWP was found to be uniform across all lower canopy positions tested (trunk, cordon and near the base of current year shoots) and positively correlated to early season shoot growth even before irrigation treatments were applied. Midday SWP was found to be more sensitive than midday leaf water potential (LWP) for detecting treatment differences over the course of the season, but both were well correlated to average seasonal leaf conductance within and between irrigation treatments. Predawn SWP and LWP were not as well correlated to average seasonal leaf conductance, but the most important factor determining midday leaf conductance was wind speed, indicating that grape leaf stomatal responses are quite sensitive to this environmental factor. Conclusion: In a wide variety of woody crop species midday stem water potential (SWP) has been found to be a valuable tool for quantifying the degree of water stress experienced by the plant, and for understanding the physiological responses of the plant to water limited conditions. In grapevine, SWP detected irrigation differences over 1 month sooner than midday leaf water potential when the number of vines used and the number of samples taken were the same for both methods, and SWP had a higher correlation to leaf conductance than predawn leaf or stem water potential. Significance and impact of study: SWP as a standard method for quantifying water stress in grapevine and other crops will aid research in the development of reliable management practices to improve crop productivity and quality.